Thirst Management Using Ice Cubes in Hemodialysis Patients: A Pre-Experimental Study - Muhammad Saefulloh; Wayunah Wayunah; Titin Hidayatin; Jihan Nadilah (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Introduction: Chronic kidney disease causes problems with fluid regulation, requiring hemodialysis patients to adhere to strict fluid intake restrictions. However, excessive thirst is often the main complaint that contributes to non-adherence to fluid restriction and increases interdialytic weight gain. Therefore, effective, safe, and easily applicable non-pharmacological interventions are needed to help reduce thirst. This study aimed to determine the effect of administering ice cubes on thirst levels in chronic kidney disease patients undergoing hemodialysis. Methods: The study employed a quasi-experimental design with one group pretest–posttest, involving 60 respondents selected through consecutive sampling. Thirst levels were measured using the Visual Analog Scale (VAS) before and after the intervention of sucking 10 ml of ice cubes for one hour. Data were analyzed using the Paired T-Test. Results: The findings showed a significant decrease in thirst levels, from a mean of 4.45 (moderate–high category) to 1.01 (very low category) after the intervention, with a p-value of 0.00 (p < 0.05). These results indicate that ice cubes are effective in reducing thirst both clinically and statistically. Conclusion: Ice-cube therapy is an effective non-pharmacological intervention to reduce thirst levels in hemodialysis patients. Recommendation: Health professionals are encouraged to apply this intervention as part of fluid management and patient comfort strategies, and to develop standardized SOPs to ensure safe and effective implementation.